A Formal Synthesis of (−)-Englerin A by RRCM and Transannular Etherification - Lee, Jungyong (2012)
[Image: see text] A bicyclization approach to englerin A has culminated in a formal asymmetric total synthesis. Key transformations in the 10-step sequence are a regiospecific epoxide opening and a relay ene-yne-ene metathesis that converts linear substrates specifically to Δ(4,6)-guaiadiene-9,10 diol derivatives. Regiospecific functionalization of the diene moiety installs the oxygen bridge required for the englerin tricyclic core.